CORRELATION OF ANTIOXIDANT AND ANTIPROLIFERATIVE ACTIVITY OF AMLA AND GINGER - Kulsum, Safeena; Suresh, Amritha; Mehta, Alka (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Our study focused on evaluating the anticancer property of ascorbic acid and aqueous extract of amla and ginger. Methods: Antioxidant capacity of ascorbic acid, aqueous extract of amla, and ginger was obtained by 2,2-diphenyl-1-picrylhydrazyl method and total antioxidant capacity (TAC). Vero cell line, PA-1, Cal-27, Cal-27 CisR, and DysMSCTR16 cell lines were treated with antioxidants to evaluate its antiproliferative property using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Colony and spheroid formation assays were also carried out in the presence of extracts to assess its role in anticancer stem cell activity. Results: Two volumes of amla 5 Î¼l (~0.016 g) and 25 Î¼l (~0.08 g) and ginger 5 Î¼l (~0.02 g) and 25 Î¼l (~0.1 g) showed TAC activity equivalent to 0.25 mM and 2 mM ascorbic acid, respectively. Amla and ascorbic acid showed significant antiproliferative property in normal (Vero) p=0.05, cancer (PA-1, Cal-27) p=0.005, and resistant (Cal-27 CisR) p=0.05 cell lines and ginger extract in Vero and Cal-27 cell lines (p=0.05). In PA-1 and Cal-27 CisR cell line, ginger extract showed proliferative activity (p=0.005). Antioxidants showed no antiproliferative activity in DysMSCTR16 cells. Amla extract and ascorbic acid showed significant inhibitory effect on spheroid (p=0.005) and colony formation capacity (p=0.0005) among dysplastic, cancer, and resistant cell lines. Ginger showed inhibitory effect (p=0.05) only in colony formation capacity. Conclusion: Overall, we found a strong correlation between antioxidant and antiproliferative activity of ascorbic acid, amla, and ginger. Amla and ascorbic acid proved to be effective in controlling cell proliferation and self-renewal properties of cancer cells. However, ginger was found to have selective and less antiproliferative effect in comparison to amla.